2015
DOI: 10.1039/c5cp02003d
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nature of the excitation energies in [Re63-Q8)X6]4− clusters: a relativistic approach

Abstract: This contribution is a relativistic theoretical study to characterize systematically the main electronic transitions in a series of hexarhenium chalcogenide [Re6(μ3-Q8)X6](4-) clusters with the aim of understanding: (i) the terminal ligand substitution effect, (ii) the substitution effect of the chalcogenide ion on the [Re6(μ3-Q8)](2+)core, and finally (iii) the significance of the spin-orbit coupling (SOC) effect on the optical selection rules. In all the cases, we found characteristic bands at around 300-550… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Studies of the electronic structure of octahedral clusters have shown that cluster core is a structural unit with delocalized molecular orbitals, e.g., their frontier molecular orbitals consist of atomic orbitals of the metal atoms and inner ligands. 5 At the same time, the cluster core is formed in the high-temperature synthesis and is a robust unit which is resistant to chemical modification under mild conditions. In combination with high symmetry, this allows one to consider the octahedral cluster cores as a structural analogue of single metal ions, or "superatoms", which can act as the basis for creating building blocks with a specified geometry and properties by variation of the terminal ligand environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies of the electronic structure of octahedral clusters have shown that cluster core is a structural unit with delocalized molecular orbitals, e.g., their frontier molecular orbitals consist of atomic orbitals of the metal atoms and inner ligands. 5 At the same time, the cluster core is formed in the high-temperature synthesis and is a robust unit which is resistant to chemical modification under mild conditions. In combination with high symmetry, this allows one to consider the octahedral cluster cores as a structural analogue of single metal ions, or "superatoms", which can act as the basis for creating building blocks with a specified geometry and properties by variation of the terminal ligand environment.…”
Section: ■ Introductionmentioning
confidence: 99%